Investigating the interaction of children through NUI in e- learning applications - Castro, Elisa Marques de Castro; Zaina, Luciana Martinez Zaina (Teste, 2018)
Although the use of natural user interfaces (NUI) has been growing, there is still a discussion of what is "natural" to a specific audience. This article presents an investigation on how children use and understand hands' natural movements (gestures) when interacting with an application, comparing them with the use of touch. The results demonstrated that there is a potential for NUI use as long as the gestures make sense to the children.